Psychophysiological diagnostics of the functional states in wrestlers - Korobeynikov, G.; Korobeinikova, L.; Shatskih, V. (International Journal of Wrestling Science, 2013)
The modern methods of diagnostics of elite wrestlers are ignored of the integral criteria of functional states. The psychophysiological diagnostics may investigate: the individual typological characteristics of higher nervous activity, the process of formation and improvement of specific skills, fatigue and overstrain in athletes. 24 elite athletes (Greco-Roman Wrestlers) were examined. The age of the athletes was 20-25. The neurodynamics functions of nervous system and parameters of autonomic regulation of the heart rhythm in wrestlers were examined. The results show that the growth rate of sensory-motor response of wrestlers is accompanied by psychomotor tension, which leads to the stability of visual reaction. The rate of sensory-motor response has communication with the tension of regulation of heart rate, which is consistent with a decrease in the duration and frequency of the oscillations RR-intervals of athletes with high speed of sensory-motor response. Conclusion. The psychophysiological diagnostics in elite wrestlers are characterized by the three components of the functional states: sensory-motor response, neurodynamics characteristics and heart rate regulation.